Recreational boating interferes with the behaviour of Atlantic cod (Gadus morhua): a study about the effects of noise pollution from small, recreational vessels on the movement patterns and vocalizations of cod in a fjord on the Norwegian Skagerrak coast - Lameijer, Remco Laurens Martijn (2021)
There is a growing concern about the impact of anthropogenic noise pollution on the marine environment. The problem is fed by a lack of knowledge, in which the effect of small recreational boats is especially underestimated. However, small recreational boats are the most abundant in vulnerable and important coastal habitats. This study addresses the issue by looking at the impact of noise on a coastal population of Atlantic cod(Gadus morhua). The results of this study indicate that vocalizations and movement patterns of cod are affected by small boat noise.. An increase in noise leads to a reduction of home range size and an increase in depth. Furthermore, the vocalization length and amount of pulses decrease during periods with high amounts of noise, while vocal fatigue increases. This impact of boat noise on cod may negatively impact courtship success due to the importance of sound during courtship interactions. Additionally, the change in depth might negatively affect cod metabolism due to changes in temperature. This may have implications for the health of cod populations residing in areas with high amounts of ambient noise. Negative impacts of noise have been previously described for other species. The negative impact on cod suggests that marine noise pollution may have economic consequences. Therefore, regulations regarding noise pollution should be urgently addressed.